2020
DOI: 10.1093/icb/icaa095
|View full text |Cite
|
Sign up to set email alerts
|

Females as the Gatekeepers to Seasonal Breeding: What We Can Learn by Studying Reproductive Mechanisms in Both Sexes

Abstract: Abstract Seasonal reproduction is a widespread adaptation in vertebrates, such that individuals time their reproductive efforts to match peak resource abundance. Individuals rely on environmental cues to regulate hormonal mechanisms governing timing of breeding. Historically, studies on physiological mechanisms of seasonal reproduction, specifically in birds, have disproportionately focused on males compared to females. For this review, I conducted a literature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Lastly, we offer solutions to address and overcome male bias in future research and increase female inclusivity. Our perspective shares important insights with many recent publications on the inclusion of female animals in biology ( Shansky, 2019 ; Orr et al, 2020 ; Rosvall et al, 2020 ) including birds ( Ball and Ketterson, 2008 ; Caro, 2012 ; Kimmitt, 2020 ). This is by no means an exhaustive list of topics for which significant improvements can be made.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Lastly, we offer solutions to address and overcome male bias in future research and increase female inclusivity. Our perspective shares important insights with many recent publications on the inclusion of female animals in biology ( Shansky, 2019 ; Orr et al, 2020 ; Rosvall et al, 2020 ) including birds ( Ball and Ketterson, 2008 ; Caro, 2012 ; Kimmitt, 2020 ). This is by no means an exhaustive list of topics for which significant improvements can be made.…”
Section: Introductionsupporting
confidence: 67%
“…This sex bias in the literature was demonstrated in a systematic review, which found that 84% of avian physiology, ecology, and reproduction studies between 2003 and 2011 involved male birds, whereas only 58% involved female birds (Caro, 2012). A 10-years follow up study found that this discrepancy persists at similar rates in the current literature (Kimmitt, 2020). In addition to being understudied, female variation in key life history traits is typically examined in the context of how such variation affects males, rather than an interesting and important subject itself (Alonzo and Warner, 2000;Rosenthal and Ryan, 2022).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Accurate predictions of future responses to climate change will require further consideration of mechanisms of female reproductive timing (Chmura et al, 2020; Kimmitt, 2020; Williams, 2012). Past and ongoing work in the junco are elucidating the physiological mechanisms driving reproductive timing in females based on life history, including endocrine systems and costs of early breeding (Graham et al, 2019; Greives et al, 2016; Kimmitt et al, 2019; Kimmitt et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Accurate predictions of future responses to climate change will require further consideration of mechanisms of female reproductive timing (Williams 2012;Chmura, Wingfield & Hahn 2020;Kimmitt 2020). Past and ongoing work in the junco is elucidating the physiological mechanisms driving reproductive timing in females based on life history, including endocrine systems and costs of early breeding (Greives et al 2016;Graham et al 2019;Kimmitt et al 2019;Kimmitt, Sinkiewicz & Ketterson 2020).…”
Section: C) Future Directionsmentioning
confidence: 99%